2014
DOI: 10.1083/jcb.2063oia128
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast heterogeneity in the cancer wound

Abstract: Fibroblasts regulate the structure and function of healthy tissues, participate transiently in tissue repair after acute inflammation, and assume an aberrant stimulatory role during chronic inflammatory states including cancer. Such cancer-associated fibroblasts (CAFs) modulate the tumor microenvironment and influence the behavior of neoplastic cells in either a tumor-promoting or tumor-inhibiting manner. These pleiotropic functions highlight the inherent plasticity of fibroblasts and may provide new avenues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Fibroblast Activation Protein α, or FAP as it is more commonly known, is a type II integral membrane protein that belongs to the membrane‐bound serine protease family. FAP has traditionally been associated with tissue repair, fibrosis and extracellular matrix degradation by fibroblasts due to its dipeptidyl peptidase and collagenase activity, but has also been shown to be upregulated in fetal mesenchymal tissues and during embryogenesis . It is one of the most strongly expressed genes in the tumor stroma and is upregulated in over 90% of epithelial carcinomas …”
Section: Fapmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblast Activation Protein α, or FAP as it is more commonly known, is a type II integral membrane protein that belongs to the membrane‐bound serine protease family. FAP has traditionally been associated with tissue repair, fibrosis and extracellular matrix degradation by fibroblasts due to its dipeptidyl peptidase and collagenase activity, but has also been shown to be upregulated in fetal mesenchymal tissues and during embryogenesis . It is one of the most strongly expressed genes in the tumor stroma and is upregulated in over 90% of epithelial carcinomas …”
Section: Fapmentioning
confidence: 99%
“…Not specific for fibroblasts and expressed by numerous other cells, such as myeloid and T-cells. 17,29 Yes…”
Section: Pdgfrα/βmentioning
confidence: 99%
“…However, each of these proteins is expressed only in a distinct subpopulation. Recent studies have revealed a strong heterogeneity within the CAF population manifested as myofibroblastic CAFs (myCAFs), inflammatory/growth factor-enriched CAFs (iCAFs), and antigen-presenting CAFs (apCAFs) (11)(12)(13)(14). Among them, myCAFs are characterized by a high expression of hyaluronan synthase 2 and αSMA and a preferential localization adjacent to cancer cells, whereas iCAFs with a low expression of αSMA are characterized by secretion of proinflammatory cytokines and are located more distant from cancer cells (15).…”
Section: Introductionmentioning
confidence: 99%